Admission Pattern and Treatment Outcome in Pediatric Intensive Care Unit in Al Zahraa Teaching Hospital, Iraq, Najaf - Neam Arkan Mohsen; Alaa Jumaah Manji Nasrawi (مجلة الكوفة الطبية)
Background: The Pediatric Intensive Care Unit (PICU) represents a specialized healthcare setting dedicated to providing critical care for infants, children, and adolescents facing severe and life-threatening medical conditions. The rate of pediatric mortality in the Pediatric Intensive Care Unit (PICU) varies worldwide, reflecting the diverse healthcare landscapes and socioeconomic factors influencing pediatric critical care outcomes. The objective of this study was to describe the pattern of admission and outcome of patients who received intensive care. Patients and Methods: A retrospective study in which records of admissions (from 1st of January 2019 to 31 December 2023) were obtained from the PICU patient's file in Al Zahraa Teaching, Najaf, Iraq. Data used from the records included age, sex, residency, address, source of admission, diagnosis, duration of stay in the unit, need for intubation and mechanical ventilation, and patient outcome.